Trends and Prospects of AI, AR & VR in Digital Marketing - Dr. Ashfaque Ahmed (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2022)
This paper provides a comprehensive review of the current trends and future prospects of Artificial Intelligence (AI), Augmented Reality (AR), and Virtual Reality (VR) in the context of digital marketing. With the rapid technological advancements, these three areas are redefining the facets of customer engagements and providing innovative tools for marketers. The study begins with an exploration of AI and its overlapping effects on personalized marketing, automated responses, customer insights, and predictive analysis. Subsequently, the phenomena of AR and VR are discussed which highlight the immersive experiences for customers, thereby driving engagement and boosting sales. The paper further conducts a comparative analysis of AI, AR, and VR, discussing their practical applications and potential bottlenecks. It culminates by identifying and discussing the opportunities and challenges these technologies pose to the marketing industry. The findings of this paper indicate that savvy adoption and implementation of these technologies can revolutionize digital marketing strategies, enhance customer experience and ultimately improve business profitability.